Study of Parenting Style and Its Effect on Emotional Regulation and Impulsiveness in Adolescents - Gopika K.; Kamini C. Tanwar (International Journal of Children, 2024)
Parenting styles vary throughout parents, and these styles can have a big impact on the growth and welfare of their kids. The study's goals include the following: (i) To determine how parenting practices affect teenagers' ability to control their emotions and impulsivity. (ii) To find out the impact of parenting style on emotional regulation and impulsiveness in adolescents. (iii) To determine the differences in impulsivity and emotional regulation between teenage boys and girls. (iv) To find out the most prevalent parenting style for adolescents. A total of 100 adolescents (50 boys and 50 girls) within the age range of 10 to 19 years along with 100 parents of the respective adolescents participated in the study. Parenting style was assessed using the Parenting Style Four Factor Questionnaire (PS-FFQ) and the adolescent’s emotional regulation was assessed using Emotion Regulation Questionnaire for Children and Adolescents (ERQ-CA) while the adolescent’s impulsiveness was assessed using Barratt Impulsiveness Scale-15 (BIS-15). Pearson correlation analysis, Regression analysis and t-test was conducted to find out the results. The findings demonstrated that among the participants, uninvolved parenting was the most common parenting style. Additionally, the findings showed no connection or influence between teenage impulsivity and emotional control and parenting style. Furthermore, there was no statistically significant difference in impulsivity or emotional regulation between teenage boys and girls, according to the results.
Keywords: Adolescents; Parenting style; cultural influences; emotional regulation; impulsiveness; peer dynamics